If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r + 2(r + -2) = 0 Reorder the terms: 4r + 2(-2 + r) = 0 4r + (-2 * 2 + r * 2) = 0 4r + (-4 + 2r) = 0 Reorder the terms: -4 + 4r + 2r = 0 Combine like terms: 4r + 2r = 6r -4 + 6r = 0 Solving -4 + 6r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6r = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 6r = 0 + 4 6r = 0 + 4 Combine like terms: 0 + 4 = 4 6r = 4 Divide each side by '6'. r = 0.6666666667 Simplifying r = 0.6666666667
| 5(6+2)= | | w^3-6w^2-27w= | | y=20x-2x^2-50 | | 5-3x=3(4-2x) | | -5=-4(x-1) | | 8s=21 | | -2(x+4)=5 | | 2=-2+24 | | 7(4+x)=20 | | 6+8x=-7+x | | 5=-2x-27 | | f(x)=2x^2-12x+15 | | 28-5x=13-10x | | x/2-x/5=9/10 | | 15-(9+10b)+(20b-4)=22 | | 5q=4+3p | | p^2+8p-5=0 | | y=37320-50x | | 3x^2-5x+k=0 | | 1/x-1/y=11 | | 24=60-4Q | | 11-3n=19 | | 2x-2=4222 | | 2x-2=422 | | 2x-2=42 | | 4x-18=5x+2 | | (x-2)+2(2x+5)=3(2x+5) | | 1x*1x-3x=0 | | a*x+b*y=c*z | | 5x-5*(2/15)*-4 | | p=15-5q/4 | | 6y=5z+14 |